Integration of Sharia Legal Principles into National Commercial Law System: A Comparative Study between Fiqh Books and Indonesian Civil Code - Madjid, Sitti Saleha; Hasanuddin, Hasanuddin; Nurwahidin, Pantja; Masuwd, Mowafg (Universitas Islam Indonesia, 2026)
This study aimed to analyze the integration of Sharia principles into national commercial law system by comparing the classical fiqh literature with Indonesian Civil Code. The urgency of this study reflected existing ambiguities in the regulation of Sharia-based contracts in national legal system, which led to legal uncertainty in commercial practices and trade agreements affecting Muslim community. The formulated problems included (1) how could Sharia principles be integrated into national commercial law? and (2) to what extent could Indonesian positive law accommodate these principles? A normative legal study was conducted using a comparative method between Islamic and national civil law, along with qualitative analysis of relevant regulations and fatwas. The results showed that there were both similarities and differences between the two legal systems, specifically concerning the principles of mutual consent and object clarity. However, Islamic law tended to be stricter in upholding the lawfulness (halal) of the contract object and in prohibiting riba (usury) and gharar (uncertainty). Based on the results, this study recommended the reconstruction of national commercial law by integrating Sharia-based contracts, harmonizing legal norms through Supreme Court, and strengthening legal education to produce practitioners competent in both legal systems. In conclusion, the integration of Sharia principles into national commercial law enriched Indonesian legal system and fostered justice that was consistent with Islamic values.